Methodology of Working With Parents of a Modern Class Head-teacher - Sherozia, Leila (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
In today’s global educational space, many new pedagogical theories and innovations have been created based on constructivist methodology, which has made the learning process more flexible and attractive; however, the same cannot be said about the ongoing process from an educational perspective: Theory of upbringingthe has been completely removed from the curriculum of higher education institutions, and this is compounded by the fact that the majority of the educational material included in textbooks lags far behind the level of educational material included in previous years in terms of moral content. The issue is relevant, therefore, the goal of our work is to bring the educational theme to the forefront in the pedagogical process, to better understand its role and importance in the process of personality formation. We will specifically discuss the role and importance of the class teacher both in the educational process and in terms of working with parents. The paper focuses on several aspects of the class teacher’s work with parents, on specific forms and methods that the teacher should use in the process of relations with parents.